2007
DOI: 10.1155/2007/410308
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of a Relapsing Hepatic Hydatid Cyst with Intrabiliary Rupture: A Case Report and Review of the Literature

Abstract: Hydatid disease, although endemic mostly in sheep-farming countries, remains a public health issue worldwide, involving mainly the liver. Intrabiliary rupture is the most frequent complication of the hepatic hydatid cyst. Endoscopy is advocated, preoperatively, to alleviate obstructive jaundice caused by intracystic materials after a frank rupture and is also a useful and well-established adjunct in locating postoperative biliary fistulas.Endoscopic retrograde cholangiography with sphincterotomy has been succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Omentoplasty also protects against infection by promoting reabsorption of serosal fluid and by inducing macrophage migration in septic foci. Manouras et al [18] reported a case of an elderly woman with frank rupture into the biliary tract. The patient was managed by Table 4 Operative procedure for managing residual hydatid cyst cavity n (%)…”
Section: Discussionmentioning
confidence: 99%
“…Omentoplasty also protects against infection by promoting reabsorption of serosal fluid and by inducing macrophage migration in septic foci. Manouras et al [18] reported a case of an elderly woman with frank rupture into the biliary tract. The patient was managed by Table 4 Operative procedure for managing residual hydatid cyst cavity n (%)…”
Section: Discussionmentioning
confidence: 99%
“…Two theories have been postulated about its pathogenesis: the first asserts that the compression of the liver hydatid cyst on the wall of the bile duct (BD) causes progressive necrosis and finally the communication between the cyst and the biliary tree; the second postulates that after the trapping of small biliary radicals in pericystic wall, high intracystic pressure causes atrophy first and then subsequently the rupture of biliary radicals [17,18].…”
Section: Definitionmentioning
confidence: 99%
“…15 When ultrasound and CT scan do not provide the necessary information, especially in case of extrahepatic cysts or the serological tests are inconclusive, then MRI can be used as an alternative diagnostic modality for the diagnosis of hydatid disease. 2,16,17 The treatment modality of hydatid disease should be selected for each patient individually according to patient preference, age, and concomitant disease. These patient related factors affect the treatment plan and also pose a risk for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%